Linguistik Terapan dalam Pembelajaran Bahasa Arab di Perguruan Tinggi: Peran, Kontribusi, dan Implikasi Kurikulum - Irdansyah Ariananda (AL-I’ROBY: Jurnal Pendidikan Bahasa Arab Dan Kebahasaaraban, 2026)
Arabic language learning in higher education has distinctive characteristics, as it is not solely oriented toward communicative competence but also functions as a medium for academic development and Islamic studies. In this context, linguistics plays an essential role as a theoretical foundation for designing, implementing, and evaluating Arabic language instruction. This study aims to examine the role of linguistics in Arabic language learning at the university level, particularly in supporting students’ language skill development. The research employs a library-based method with a qualitative descriptive approach through an analysis of relevant literature and previous studies on linguistics, Arabic language curricula, and Arabic language teaching practices in higher education. The findings indicate that an understanding of linguistic components—such as phonology, morphology, syntax, semantics, and vocabulary—contributes significantly to the effectiveness of Arabic language learning. Furthermore, the integration of linguistic perspectives into curriculum design and instructional strategies assists lecturers in identifying students’ learning difficulties and in developing more communicative and contextual learning processes. Therefore, the systematic application of linguistics in Arabic language learning at the higher education level is a key factor in enhancing students’ overall Arabic language competence